Anti-Asian American Hate Crimes Spike During the Early Stages of the COVID-19 Pandemic - Han, Sungil; Riddell, Jordan R.; Piquero, Alex R. (Journal of interpersonal violence, 2023)
The recent high-profile cases of hate crimes in the U.S., especially those targeting Asian Americans, have raised concerns about their risk of victimization. Following the onset of the COVID-19 pandemic, intimations—and even accusations—that the novel coronavirus is an “Asian” or “Chinese” virus have been linked to anti-Asian American hate crime, potentially leaving members of this group not only fearful of being victimized but also at risk for victimization. According to the Stop AAPI Hate Center, nearly 1900 hate crimes against Asian Americans were reported by victims, and around 69% of cases were related to verbal harassment, including being called the “Chinese Coronavirus.” Yet, most of the evidence martialed on spikes in anti-Asian American hate crime during the COVID-19 pandemic has been descriptive. Using data from four U.S. cities that have large Asian American populations (New York, San Francisco, Seattle, and Washington D.C.), this study finds that hate crime against Asian Americans increased considerably in 2020 compared with that of 2019. Specifically, hate crime against Asian Americans temporarily surged after March 16, 2020, when the blaming labels including “Kung flu” or “Chinese Virus” were used publicly. However, the significant spike after March 16, 2020, in anti-Asian American hate crime was not sustained over the follow-up time period available for analysis.